Extraction and Determination of Oxymatrine Pesticide in Environmental Sample and in its Formulation using High-Performance Liquid Chromatography - Shaheed, Ihsan M.; Dhahir, Saadiyah A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
The quinolizindine alkaloid compound, oxymatrine pesticide, was analysis in the river water samples collected from different agriculture areas in the Iraqi city of Kerbala and also in its formulation using developed reverse-phase high-performance liquid chromatography method. Acetonitrile:methanol (60:40 v/v) was chosen as mobile phase at pH (7.0), flow rate 0.5 mL/min, and 20 µL as volume injection. Modified ecological-friendly method, dispersive liquid-liquid microextraction, was used for the extraction of oxymatrine from water samples. Linearity study was constructed from 0.1 to 70 μg/mL at λmax 205 nm. The limit of detection and limit of quantification were 0.025 and 0.082 μg/mL, respectively, and the relative standard deviation (RSD) % was 0.518%. Three spiked levels of concentration (20.0, 40.0, and 70.0 μg/mL) were used for the validation method. The percentage recovery for the three spiked samples was ranged between 98.743 and 99.432 and the RSD% was between 0.051 and 0.202%, the formulation studies of oxymatrine between 99.487 and 99.798, and the RSD% was ranged from 0.045 to 0.057%. The developed method can be used accurately and selectively for the determination of oxymatrine in environmental samples and in the formulation.